Lithium ion secondary battery
By setting an insulating layer on the positive electrode sheet of the lithium-ion battery, the particle size regulation of inorganic particles is used to reduce burrs, and combined with the design of the ceramic layer, the short-circuit and lithium extraction problems caused by burrs in the battery are solved, and the safety performance and cycle life of the battery are improved.
Patent Information
- Application Number
- CN202411706332.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
AI Technical Summary
Lithium-ion batteries are prone to burrs in the position where the paste area on the electrode sheet is connected to the empty foil area, resulting in short-circuiting and safety problems inside the battery. The existing protective tape is prone to side reactions with the electrolyte under a high voltage system, resulting in decomposition failure and lithium evolution problems.
An insulating layer with the first inorganic particles is provided at the location where the positive electrode sheet paste area is connected to the empty foil area, and by regulating the particle size relationship between the first inorganic particles and the second inorganic particles in the separator ceramic layer, an insulating layer is used instead of the protective tape to reduce burrs and improve the self-discharge and lithium-ion problems of the battery.
It effectively reduces the burrs at the contact position between the paste area on the positive electrode sheet and the empty foil area, improves the self-discharge and lithium extraction problems of the battery, and improves the cycle life and safety performance of the battery.
Smart Images

Figure CN119542509A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a lithium-ion secondary battery. Background Art
[0002] Lithium-ion batteries are prone to burrs during the production process, especially at the junction of the paste area and the empty foil area on the electrode. These burrs can pierce the diaphragm and cause a short circuit inside the battery, causing safety problems. For this reason, protective tape is generally affixed to the areas where burrs are likely to appear on the positive and negative electrodes of lithium-ion batteries to avoid safety problems caused by burrs piercing the diaphragm. However, as the battery voltage system increases, the risk of side reactions between the protective tape and the electrolyte on the surface of the positive electrode active material increases, causing the protective tape to decompose and fail, resulting in lithium precipitation and bubbling at the edge of the protective tape, greatly reducing the battery's service life and safety performance. Summary of the invention
[0003] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art, and to provide a lithium ion secondary battery (hereinafter referred to as a battery). The lithium ion secondary battery of the present invention has a special design for the structure of the positive electrode sheet, and an insulating layer having first inorganic particles is arranged at the position where the paste area of the positive electrode sheet is connected to the empty foil area, and by regulating the particle size relationship between the first inorganic particles and the second inorganic particles in the diaphragm ceramic layer arranged directly opposite to the positive electrode sheet, the insulating layer is used to replace the protective tape, which can effectively solve the problems caused by the protective tape, and effectively reduce the burrs at the position where the paste area and the empty foil area on the positive electrode sheet are connected, improve the self-discharge and lithium precipitation problems of the battery, and improve the cycle life and safety performance of the battery.
[0004] In the related art, protective tape is used to solve the problem of burrs being easily generated at the junction of the paste-coated area and the empty foil area on the electrode. However, the use of protective tape will reduce the service life and safety performance of the battery. Therefore, the inventors of the present invention believe that insulating materials that are not easy to react with the electrolyte can be used to replace the protective tape, such as inorganic particles. However, due to the small particle size of the inorganic particles, when they are set at a position on the positive electrode that is prone to burrs, the inorganic particles with a smaller particle size cannot completely cover the generated burrs. Therefore, if inorganic particles are simply set at a position where burrs are prone to occur, the problem of burrs piercing the diaphragm cannot be effectively solved.
[0005] By providing a ceramic layer on the diaphragm and using it in combination with the positive electrode sheet, the generation of burrs can be improved to a certain extent, but the improvement effect is not ideal. The inventors have conducted a lot of research and found that the reason for the unsatisfactory improvement effect may be that the inorganic particles provided at the junction of the paste area and the empty foil area can only cover part of the burrs of a specific size. When the uncovered burrs of other sizes come into contact with the ceramic layer on the diaphragm, since the hardness of the ceramic layer is greater than that of the active material layer, this part of the uncovered burrs will be flattened by the ceramic layer, but due to the existence of the extrusion force, the inorganic particles located at the junction of the paste area and the empty foil area will cause protrusions, thereby piercing the diaphragm and causing self-discharge. Based on the above findings, the inventors of the present invention proposed the following scheme:
[0006] The present invention provides a lithium-ion secondary battery, comprising a positive electrode sheet, a separator and a negative electrode sheet which are stacked and wound; along the winding direction of the lithium-ion secondary battery, the current collector of the positive electrode sheet is provided with a positive electrode active layer and an insulating layer; the insulating layer partially covers the positive electrode active layer and partially covers the current collector; the insulating layer comprises first inorganic particles, and the median particle size of the first inorganic particles is a first Dv50; the separator comprises a substrate layer and a ceramic layer located on at least one side of the substrate layer, and the ceramic layer faces the positive electrode sheet; the ceramic layer comprises second inorganic particles, and the median particle size of the second inorganic particles is a second Dv50; the second Dv50 / the first Dv50 is 0.25-10, and the second Dv50≠the first Dv50.
[0007] By adjusting the ratio of the median particle size of the second inorganic particles to the first inorganic particles, the two can be matched, so that burrs of various sizes can be well embedded in the insulating layer and the ceramic layer, which can effectively prevent the inorganic particles from piercing the diaphragm due to the extrusion force. In addition, by adjusting the ratio of the median particle size of the second inorganic particles to the first inorganic particles, it is more conducive to providing a rich pore structure and storing electrolyte to reduce the risk of lithium precipitation. At the same time, it is also beneficial to reduce the thickness of the ceramic layer on the diaphragm to reduce the thickness of the battery, thereby increasing the volume energy density of the battery.
[0008] Through the above technical scheme, the present invention has at least the following advantages compared with the prior art: the battery of the present invention effectively reduces the burrs at the junction of the paste area and the empty foil area on the positive electrode sheet, improves the self-discharge and lithium plating problems of the battery, and improves the cycle life and safety performance of the battery.
[0009] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 FIG. 1 is a schematic diagram of a positive electrode sheet in an example of the present invention, wherein: Figure 1 (a) is a top view; Figure 1 (b) is a side view.
[0011] Figure 2 Shown is a schematic diagram of a partial structure of a lithium-ion secondary battery in an example of the present invention.
[0012] Figure 3 Shown is a scanning electron microscope (SEM) image of a cross section of a positive electrode sheet in an example of the present invention.
[0013] Figure 4 FIG. 1 is a schematic diagram of a winding core in an embodiment of the present invention.
[0014] Figure 5 FIG. 1 is a schematic diagram of the structure of a diaphragm in an example of the present invention, wherein: Figure 5 (a) and Figure 5 (b) The middle rubber layer is set on one side; Figure 5 (c) and Figure 5 (d) Set on both sides of the middle rubber layer. DETAILED DESCRIPTION
[0015] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0016] The present invention provides a lithium-ion secondary battery, which may include a positive electrode sheet, a separator and a negative electrode sheet stacked and wound. Along the winding direction of the lithium-ion secondary battery, the current collector of the positive electrode sheet has a positive electrode active layer and an insulating layer; the insulating layer partially covers the positive electrode active layer and partially covers the current collector. Figure 1 FIG. 1 is a schematic diagram of a positive electrode sheet in an example of the present invention, wherein: Figure 1 (a) is a top view; Figure 1(b) is a side view. It can be seen from the figure that along the winding direction of the battery, the current collector 1-3 of the positive electrode sheet has a positive electrode active layer 1-1 and an insulating layer 1-2; the insulating layer 1-2 partially covers the positive electrode active layer 1-1, and partially covers the current collector 1-3 (when there is no insulating layer 1-2, the area where the positive electrode active layer 1-1 is located is the paste area, and the area on the current collector 1-3 without the positive electrode active layer 1-1 is the empty foil area). Figure 1 (a) and Figure 1 (b) shows an example in which the insulating layer 1-2 is located at the tail end of the winding. The insulating layer 1-2 can also be located at the head end of the winding. Figure 1 (b) shows an example in which the positive electrode active layer 1-1 and the insulating layer 1-2 are arranged on one side. The positive electrode active layer 1-1 and the insulating layer 1-2 may also be located on both sides of the current collector 1-3.
[0017] In the present invention, the insulating layer may include first inorganic particles, and the median particle size of the first inorganic particles is a first Dv50.
[0018] In the present invention, the separator may include a substrate layer and a ceramic layer located on at least one side of the substrate layer, wherein the ceramic layer faces the positive electrode sheet. Figure 2 The figure shows a partial structural schematic diagram of a lithium-ion secondary battery in an example of the present invention. As can be seen from the figure, the battery includes a positive electrode sheet 2, a separator 3 and a negative electrode sheet 4, the separator 3 includes a substrate layer 3-1 and a ceramic layer 3-2 located on one side of the substrate layer 3-1, and the ceramic layer 3-2 faces the positive electrode sheet 2. It can be understood that Figure 2 Only the case where the ceramic layer is disposed on one side of the substrate layer is shown, and the ceramic layer may also be disposed on both sides of the substrate layer. The ceramic layer may include second inorganic particles, and the median particle size of the second inorganic particles is a second Dv50.
[0019] In the present invention, the second Dv50 / the first Dv50 can be 0.25-10, for example, 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, and the second Dv50≠the first Dv50.
[0020] In one example, the second Dv50 / the first Dv50 is 0.25-4.
[0021] In one example, the second Dv50 / the first Dv50 is 0.25-3.
[0022] In the present invention, the first Dv50 may be 0.2 μm-5 μm, for example, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.5 μm, 2 μm, 3 μm, 4 μm or 5 μm.
[0023] In one example, the first Dv50 is 0.5 μm-2 μm.
[0024] In the present invention, the second Dv50 may be 0.2 μm-5 μm, for example, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.5 μm, 2 μm, 3 μm, 4 μm or 5 μm.
[0025] In one example, the second Dv50 is 0.5 μm-2 μm.
[0026] In the present invention, the first Dv50 and the second Dv50 can be tested by conventional methods in the art, for example, by a laser particle size analyzer, specifically as follows: the insulating layer and the ceramic layer are scraped off by a blade, and subjected to grinding and other treatments to obtain first inorganic particles and second inorganic particles, respectively, and the obtained first inorganic particles and second inorganic particles are respectively sent to a laser particle size analyzer for detection.
[0027] In the present invention, the first inorganic particles and the second inorganic particles may each independently include at least one of magnesium oxide, magnesium hydroxide, aluminum oxide, tungsten oxide, titanium oxide, silicon dioxide, and boehmite.
[0028] In one example, the first inorganic particles and the second inorganic particles each independently include at least one of silicon dioxide, magnesium oxide, aluminum oxide, and boehmite.
[0029] In one example, the first inorganic particles and the second inorganic particles each independently include at least one of alumina and boehmite.
[0030] In the present invention, the insulating layer may further include a first binder. The ceramic layer may further include a second binder.
[0031] In one example, the first binder and the second binder each independently include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), styrene-butadiene rubber (SBR), polymethyl methacrylate (PMMA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose (CMC-Na), lithium carboxymethyl cellulose (CMC-Li), polyimide (PI) and at least one of the derivatives of the above substances.
[0032] In one example, the first binder and the second binder each independently include at least one of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), styrene-butadiene rubber (SBR), polymethyl methacrylate (PMMA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose (CMC-Na), lithium carboxymethyl cellulose (CMC-Li) and polyimide (PI).
[0033] In one example, the first binder and the second binder each independently include at least one of PVDF, PVDF-HFP and PMMA.
[0034] In one example, the first binder and the second binder each independently include PVDF.
[0035] Under the premise of controlling the ratio of the median particle size of the second inorganic particles to the first inorganic particles within a specific range, in order to further improve the cycle stability of the battery, it is necessary to limit the content of the binder in the insulating layer and the ceramic layer. This is because when an insulating layer is used to replace the protective tape, it is necessary not only to consider the impact of burrs on the battery, but also to ensure the bonding ability between the insulating layer and the diaphragm, so as to prevent the battery from deforming and maintain the normal charge and discharge cycle of the battery.
[0036] In the present invention, based on the total mass of the insulating layer, the content of the first adhesive can be 5%-30%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 25% or 30%.
[0037] In one example, based on the total mass of the insulating layer, the content of the first binder is 8%-15%.
[0038] In the present invention, based on the total mass of the ceramic layer, the content of the second binder can be 1%-20%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.
[0039] In one example, based on the total mass of the ceramic layer, the content of the second binder is 2%-10%.
[0040] In one example, a mass content of the first binder in the insulating layer is greater than a mass content of the second binder in the ceramic layer.
[0041] The inventors of the present invention have discovered that by adjusting the mass content of the first binder in the insulating layer to be greater than the mass content of the second binder in the ceramic layer, the pore blocking problem of the diaphragm can be effectively improved while ensuring stable bonding between the positive electrode sheet and the diaphragm, which is beneficial to improving lithium plating of the battery.
[0042] In one example, both the first binder and the second binder include F element.
[0043] In the present invention, the ratio of the mass content of the F element in the insulating layer to the mass content of the F element in the ceramic layer can be 1:(0.2-1.2), for example, 1:0.2, 1:0.25, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.67, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1 or 1:1.2.
[0044] In one example, the ratio of the mass content of the F element in the insulating layer to the mass content of the F element in the ceramic layer is 1:(0.25-0.67).
[0045] The inventors of the present invention have found that when the ratio of the mass content of the F element in the insulating layer to the mass content of the F element in the ceramic layer is within a specific range, the self-discharge and lithium precipitation problems can be further improved. The reasons may be: First, by controlling the mass content ratio of the F element, the adhesion between the positive electrode sheet and the separator can be guaranteed to prevent the positive electrode sheet and the separator from being misaligned, resulting in the burrs at the junction of the positive electrode active layer and the empty foil area piercing the separator and causing an internal short circuit in the battery. Second, by controlling the mass content ratio of the F element, the transmission of lithium ions in the insulating layer can be effectively blocked, thereby preventing the occurrence of lithium precipitation.
[0046] In the present invention, the mass content of the F element in the insulating layer and the mass content of the F element in the ceramic layer can be measured by conventional methods in the art, such as energy dispersive spectrometer (EDS).
[0047] In the present invention, the thickness of the positive electrode active layer may be 30 μm-75 μm, for example, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm or 75 μm.
[0048] In one example, the thickness of the positive electrode active layer is 35 μm-60 μm.
[0049] In the present invention, the thickness of the insulating layer may be 1 μm-15 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm.
[0050] In one example, the thickness of the insulating layer is 3 μm-12 μm.
[0051] In the present invention, the thickness of the positive electrode active layer refers to the thickness of the portion located on the surface of one side of the current collector and not covered by the insulating layer. The thickness of the insulating layer refers to the thickness of the portion located on one side of the current collector and covering the current collector.
[0052] In the present invention, in the winding direction of the lithium ion secondary battery, the size of the insulating layer portion covering the positive electrode active layer is d1, and the size of the insulating layer portion covering the current collector is d2. d1 and d2 satisfy: d2 / d1 is 0.6-6, for example, 0.6, 0.67, 0.8, 0.85, 0.86, 1, 2, 3, 4, 5 or 6.
[0053] In one example, d2 / d1 is 0.85-5.
[0054] By adjusting d2 / d1, it can be ensured that the position where the paste-coated area and the empty foil area on the negative electrode sheet meet falls within the insulating layer, so as to reduce the risk of short circuit of the battery when the burrs at the position where the paste-coated area and the empty foil area meet pierce the diaphragm.
[0055] In the present invention, d1 may be 2 mm-15 mm, for example, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm or 15 mm.
[0056] In one example, d1 is 3 mm-7 mm.
[0057] In the present invention, d2 may be 4 mm-30 mm, for example, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 15 mm, 20 mm, 25 mm or 30 mm.
[0058] In one example, d2 is 6 mm-15 mm.
[0059] In the present invention, the insulating layer covering the positive electrode active layer is partially embedded in the positive electrode active layer.
[0060] In one example, the first inorganic particles are embedded in the positive electrode active layer. Figure 3 The figure shows a scanning electron microscope (SEM) image of a cross section of a positive electrode sheet in an example of the present invention. It can be seen from the figure that the first inorganic particles are embedded in the positive electrode active layer.
[0061] By further controlling the position of the first inorganic particles so that the first inorganic particles are embedded in the positive electrode active layer, the conductive network of the positive electrode active layer in this region can be disrupted, reducing its conductivity and increasing its impedance, further blocking the transport of lithium ions in the insulating layer, thereby preventing the occurrence of lithium deposition.
[0062] In the present invention, the vertical distance from the first inorganic particles in the insulating layer covering the positive electrode active layer to the surface of the insulating layer can be 2 μm - 15 μm, such as 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm.
[0063] In one example, the vertical distance from the first inorganic particles in the insulating layer covering the positive electrode active layer to the surface of the insulating layer is 3 μm - 8 μm.
[0064] On the premise of controlling the ratio of the median particle sizes of the second inorganic particles and the first inorganic particles within a specific range, by regulating the vertical distance from the first inorganic particles to the surface of the insulating layer, it is possible to further prevent too many burrs from piercing through the gaps of the first inorganic particles to the surface of the insulating layer, resulting in the occurrence of micro-short circuits. While ensuring a low self-discharge of the battery, it does not increase the ineffective thickness of the positive electrode sheet, which is beneficial to reducing the battery thickness to improve the volumetric energy density.
[0065] In the present invention, the vertical distance from the first inorganic particles to the surface of the insulating layer can be obtained by testing through conventional methods in the art. For example, using SEM, within the field of view, at least 10 first inorganic particles are randomly selected, and the minimum value of the vertical distance from the surface of each first inorganic particle to the surface of the insulating layer is measured, and the average value is taken.
[0066] In the present invention, the positive electrode sheet may further include a positive electrode active material, and the positive electrode active material may include a substance with the chemical formula Li a Ni b Co c Mn d M e O2, where 0.8 ≤ a ≤ 1.3, 0.8 ≤ b ≤ 0.98, 0.01 ≤ c ≤ 0.2, 0.005 ≤ d ≤ 0.14, 0 < e ≤ 0.08, and M may include at least one of Al, Zr, B, Y, Sr, W, Ti, Mg, La, Fe, and Nb.
[0067] When 0.8≤b≤0.98 in the positive electrode active material, the demand for electrolyte will increase. When the electrolyte is lacking, it is easy to cause side reactions, which will further lead to the consumption of electrolyte, causing black spots and lithium precipitation. The junction of the paste area and the empty foil area on the positive electrode sheet is more likely to cause lithium precipitation and black spots due to lack of electrolyte. At this time, the insulating layer can increase the residual liquid amount at this location, thereby improving the lithium precipitation and black spot problems caused by lack of electrolyte.
[0068] In the present invention, the thickness of the ceramic layer may be 1 μm-5 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.
[0069] In the present invention, the insulating layer may be located at the winding beginning and / or the winding end of the positive electrode sheet.
[0070] In the present invention, the positive electrode sheet, the separator and the negative electrode sheet are stacked and wound to form a winding core, and the insulating layer may be located at the winding head end and / or the winding tail end of the winding core. Figure 4 FIG. 1 is a schematic diagram of a winding core in an example of the present invention. The insulating layer may be located at the winding beginning and / or winding end of the winding core in the figure.
[0071] In the present invention, in the winding direction of the lithium-ion secondary battery, the size of the ceramic layer exceeds the size of the positive electrode sheet.
[0072] In the present invention, the diaphragm may further include a glue layer, and the glue layer may be located on the outermost surface of at least one side of the diaphragm. Figure 5 FIG. 1 is a schematic diagram of the structure of a diaphragm in an embodiment of the present invention, wherein Figure 5 (a) and Figure 5 (b) The middle rubber layer is set on one side. Figure 5 (c) and Figure 5 (d) The rubber layer is set on both sides. Figure 5 (a) The diaphragm includes a substrate layer 3-1, a ceramic layer 3-2 located on one side of the substrate layer 3-1, and a glue layer 3-3 located on the outer surface of the ceramic layer 3-2. Figure 5 (b) The diaphragm includes a substrate layer 3-1, a ceramic layer 3-2 located on both sides of the substrate layer 3-1, and a glue layer 3-3 located on the outer surface of one side of the diaphragm. Figure 5 (c) The diaphragm includes a substrate layer 3-1, a ceramic layer 3-2 located on one surface of the substrate layer 3-1, and a glue layer 3-3 located on both sides of the outer surface of the diaphragm. Figure 5 (d) The middle diaphragm includes a substrate layer 3-1, a ceramic layer 3-2 located on both side surfaces of the substrate layer 3-1, and a glue layer 3-3 located on the outer surface of the ceramic layer 3-2.
[0073] The adhesive layer may include a binder, and the binder may include at least one of PVDF, PVDF-HFP, SBR, PMMA, PAA, CMC, CMC-Na, CMC-Li, PI and derivatives thereof.
[0074] In one example, the binder includes at least one of PVDF, PVDF-HFP, SBR, PMMA, PAA, CMC, CMC-Na, CMC-Li and PI.
[0075] In the present invention, the positive electrode active material layer may include the positive electrode active material, a positive electrode conductive agent and a positive electrode binder. The positive electrode conductive agent may include a conductive agent conventionally used in the art, for example, including at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber and carbon nanotubes (including single-walled carbon nanotubes and / or multi-walled carbon nanotubes). The positive electrode binder may include a binder conventionally used in the art, for example, including at least one of PVDF, CMC-Na, SBR, polytetrafluoroethylene and polyethylene oxide.
[0076] In the present invention, based on the total mass of the positive electrode active material layer, the content of the positive electrode active material can be 80%-99.8% (for example, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, 99% or 99.8%), the content of the positive electrode conductor can be 0.1%-10% (for example, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5% or 0.1%), and the content of the positive electrode binder can be 0.1%-10% (for example, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5% or 0.1%).
[0077] In the present invention, the battery may further include a negative electrode sheet and an electrolyte. The negative electrode sheet and the electrolyte may include those conventionally used in the art.
[0078] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.
[0079] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0080] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.
[0081] Example
[0082] The following examples are used to illustrate the lithium ion secondary battery of the present invention.
[0083] Example 1
[0084] Prepare the battery as follows:
[0085] (1) Preparation of positive electrode sheet
[0086] The positive electrode active material (LiNi 0.9 Co 0.05 Mn 0.02 Al 0.03 O2), PVDF and conductive carbon black are mixed in a mass ratio of 97.5:1.5:1, N-methylpyrrolidone (NMP) is added to prepare a positive electrode active material slurry (solid content is 60wt%), the above positive electrode active material slurry is evenly coated on the surface of aluminum foil and dried; boehmite (the first Dv50 is 0.5μm) and PVDF are mixed in a mass ratio of 88:12, NMP is added to prepare an insulating layer slurry (solid content is 60wt%), the above insulating layer slurry is coated on the tail of the positive electrode active layer, dried, and compacted by a roller press to obtain a positive electrode sheet, wherein d1 is 5mm, d2 is 10mm, and d2 / d1 is 2; the thickness of the positive electrode active layer is 50μm, and the thickness of the insulating layer is 8μm; boehmite is embedded in the positive electrode active layer, and the vertical distance from the boehmite particles to the surface of the insulating layer is 5μm.
[0087] (2) Preparation of negative electrode sheet
[0088] Artificial graphite, silicon-carbon material, SBR and conductive carbon black are mixed in a mass ratio of 85:10:3:2 to form a uniform and stable mixture, deionized water is added to prepare a negative electrode active material slurry (solid content is 46wt%), the above negative electrode active material slurry is evenly coated on both sides of the copper foil, and after drying and roller pressing, a negative electrode sheet is obtained.
[0089] (3) Preparation of electrolyte
[0090] In a glove box filled with argon (H2O < 0.1 ppm, O2 < 0.1 ppm), ethylene carbonate, dimethyl carbonate and 1,2-propylene carbonate were mixed in a volume ratio of 1:1:1, 1 M lithium hexafluorophosphate was added, stirred evenly, and the electrolyte was obtained after passing the moisture and free acid tests.
[0091] (4) Preparation of diaphragm
[0092] Alumina (the second Dv50 is 1.5μm) and PVDF are mixed in a mass ratio of 94:6, NMP is added to prepare a ceramic layer slurry (solid content is 60wt%), the ceramic layer slurry is coated on one side of the polyethylene film, PVDF is added to NMP to obtain a glue layer slurry (solid content is 60wt%), the glue layer slurry is coated on the outer surface of the ceramic layer and the other side of the polyethylene film, and dried to obtain a diaphragm, wherein the thickness of the ceramic layer is 3μm; the second Dv50 / the first Dv50 is 3, and the ratio of the mass content of the F element in the insulating layer to the mass content of the F element in the ceramic layer is 1:0.5.
[0093] (5) Preparation of batteries
[0094] The positive electrode sheet prepared in step (1), the diaphragm prepared in step (4) and the negative electrode sheet prepared in step (2) are wound to form a winding core, and the aluminum pole ear and the copper-plated nickel pole ear are welded after hot pressing; after liquid injection, the battery is formed, sorted, and OCV tested to obtain a battery, wherein the insulating layer is located at the winding tail end of the winding core, and in the winding direction, the size of the ceramic layer exceeds the size of the positive electrode sheet, and the ceramic layer of the diaphragm faces the positive electrode sheet.
[0095] Example 2
[0096] The method is carried out with reference to Example 1, except that step (1) and step (4) are specifically as follows:
[0097] (1) Preparation of positive electrode sheet
[0098] The positive electrode active material (LiNi 0.85 Co 0.1 Mn 0.02 Ti 0.03 Aluminum oxide (AAO) and PVDF (PVDF) were mixed at a mass ratio of 97.5:1.5:1, and N-methylpyrrolidone (NMP) was added to prepare a positive electrode active material slurry (solid content of 60 wt%), which was evenly coated on the surface of the aluminum foil and dried; aluminum oxide (the first Dv50 was 1 μm) and PVDF were mixed at a mass ratio of 92:8, and NMP was added to prepare an insulating layer slurry (solid content of 60 wt%), which was coated on the tail of the positive electrode active layer, dried, and compacted by a roller press to obtain a positive electrode sheet, wherein d1 was 3 mm, d2 was 15 mm, and d2 / d1 was 5; the thickness of the positive electrode active layer was 50 μm, and the thickness of the insulating layer was 3 μm; aluminum oxide was embedded in the positive electrode active layer, and the vertical distance from the aluminum oxide particles to the surface of the insulating layer was 3 μm.
[0099] (4) Preparation of diaphragm
[0100] Boehmite (the second Dv50 is 2 μm) and PVDF are mixed in a mass ratio of 98:2, and NMP is added to prepare a ceramic layer slurry (solid content is 60wt%), and the above ceramic layer slurry is applied to one side of the polyethylene film. PVDF is added to NMP to obtain an adhesive layer slurry (solid content is 60wt%), and the above adhesive layer slurry is applied to the outer surface of the ceramic layer and the other side of the polyethylene film, and dried to obtain a diaphragm, wherein the thickness of the ceramic layer is 1 μm; the second Dv50 / the first Dv50 is 2, and the ratio of the mass content of the F element in the insulating layer to the mass content of the F element in the ceramic layer is 1:0.25.
[0101] Example 3
[0102] The method is carried out with reference to Example 1, except that step (1) and step (4) are specifically as follows:
[0103] (1) Preparation of positive electrode sheet
[0104] The positive electrode active material (LiNi 0.95 Co 0.02 Mn 0.02 Mg 0.01 A mixture of aluminum oxide and boehmite (wherein the mass ratio of aluminum oxide to boehmite is 1:1) (the first Dv50 is 2 μm) and PVDF are mixed in a mass ratio of 85:15, NMP is added to prepare an insulating layer slurry (solid content is 60 wt%), the insulating layer slurry is coated on the tail of the positive electrode active layer, dried, and compacted by a roller press to obtain a positive electrode sheet, wherein d1 is 7 mm, d2 is 6 mm, and d2 / d1 is 0.86; the thickness of the positive electrode active layer is 50 μm, and the thickness of the insulating layer is 12 μm; the first inorganic particles are embedded in the positive electrode active layer, and the vertical distance from the first inorganic particles to the surface of the insulating layer is 8 μm.
[0105] (4) Preparation of diaphragm
[0106] A mixture of alumina and boehmite (wherein the mass ratio of alumina to boehmite is 1:1) (the second Dv50 is 0.5 μm) and PVDF are mixed in a mass ratio of 90:10, and NMP is added to prepare a ceramic layer slurry (solid content is 60 wt%), and the above ceramic layer slurry is applied to one side of the polyethylene film. PVDF is added to NMP to obtain a glue layer slurry (solid content is 60 wt%), and the above glue layer slurry is applied to the outer surface of the ceramic layer and the other side of the polyethylene film, and dried to obtain a diaphragm, wherein the thickness of the ceramic layer is 5 μm; the second Dv50 / the first Dv50 is 0.25, and the ratio of the mass content of the F element in the insulating layer to the mass content of the F element in the ceramic layer is 1:0.67.
[0107] Example 4
[0108] Used to verify the impact of changes in "Second Dv50 / First Dv50".
[0109] The method is carried out in accordance with Example 1, except that the second Dv50 of the aluminum oxide in the diaphragm ceramic layer is changed, as follows:
[0110] The second Dv50 of aluminum oxide is 2 μm, and the second Dv50 / first Dv50 is 4.
[0111] Example 5 Group
[0112] This group of embodiments is used to verify the impact of the change of the “first Dv50”.
[0113] This group of examples is carried out with reference to Example 1, except that the first Dv50 of boehmite is changed, as follows:
[0114] Example 5a, the first Dv50 of boehmite is 0.2 μm, and the second Dv50 / first Dv50 is 7.5;
[0115] In Example 5b, the first Dv50 of boehmite is 5 μm, and the second Dv50 / first Dv50 is 0.3.
[0116] Example 6 Group
[0117] This group of embodiments is used to verify the impact of the change of the “second Dv50”.
[0118] This group of examples is carried out with reference to Example 1, except that the second Dv50 of aluminum oxide is changed, as follows:
[0119] Example 6a, the second Dv50 of aluminum oxide is 0.2 μm, and the second Dv50 / first Dv50 is 0.4;
[0120] In Example 6b, the second Dv50 of aluminum oxide is 5 μm, and the second Dv50 / first Dv50 is 10.
[0121] Example 7 Group
[0122] This group of examples is used to verify the influence of changes in “the type of the first inorganic particles and the type of the second inorganic particles”.
[0123] This group of examples is carried out with reference to Example 1, except that the types of the first inorganic particles and the second inorganic particles are changed, as follows:
[0124] Example 7a, the first inorganic particle is replaced by the same mass and the same first Dv50 of silicon dioxide, and the second inorganic particle is replaced by the same mass and the same first Dv50 of silicon dioxide;
[0125] Example 7b, the first inorganic particles are replaced by magnesium oxide of the same mass and the same first Dv50, and the second inorganic particles are replaced by magnesium oxide of the same mass and the same first Dv50.
[0126] Example 8 Group
[0127] This group of examples is used to verify the impact of changing the "type of the first adhesive".
[0128] This group of examples is carried out with reference to Example 1, except that the type of the first binder is changed, as follows:
[0129] In Example 8a, the first binder is replaced with PVDF-HFP of the same mass, wherein the ratio of the mass content of the F element in the insulating layer to the mass content of the F element in the ceramic layer is 1:0.43;
[0130] In Example 8b, the first binder is replaced by a mixture of PVDF and PMMA of the same mass (the mass ratio of PVDF to PMMA is 2:1), wherein the ratio of the mass content of the F element in the insulating layer to the mass content of the F element in the ceramic layer is 1:0.67.
[0131] Example 9 Group
[0132] This group of embodiments is used to verify the influence of the change of "the ratio of the mass content of the F element in the insulating layer to the mass content of the F element in the ceramic layer".
[0133] This group of examples is carried out with reference to Example 1, except that the ratio of the mass content of the F element in the insulating layer to the mass content of the F element in the ceramic layer is regulated by changing the mass content of the first binder in the insulating layer, as follows:
[0134] Example 9a, boehmite (first Dv50 is 0.5 μm) and PVDF in a mass ratio of 95:5, wherein the ratio of the mass content of the F element in the insulating layer to the mass content of the F element in the ceramic layer is 1:1.2;
[0135] Example 9b, boehmite (first Dv50 is 0.5 μm) and PVDF are in a mass ratio of 70:30, wherein the ratio of the mass content of the F element in the insulating layer to the mass content of the F element in the ceramic layer is 1:0.2.
[0136] Example 10 Group
[0137] This group of embodiments is used to verify the impact of changes in the "thickness of the insulating layer".
[0138] This group of embodiments is carried out with reference to Embodiment 1, except that the thickness of the insulating layer is changed, as follows:
[0139] In embodiment 10a, the thickness of the insulating layer is 1 μm;
[0140] In Example 10b, the thickness of the insulating layer is 15 μm.
[0141] Example 11 Group
[0142] This group of embodiments is used to verify the impact of the change of "d1".
[0143] This group of examples is carried out with reference to Example 1, except that d1 is changed, as follows:
[0144] Example 11a, d1 is 2 mm, d2 / d1 is 5;
[0145] In Example 11b, d1 is 15 mm and d2 / d1 is 0.67.
[0146] Example 12 Group
[0147] This group of embodiments is used to verify the impact of the change of "d2".
[0148] This group of examples is carried out with reference to Example 1, except that d2 is changed, as follows:
[0149] Example 12a, d2 is 4 mm, d2 / d1 is 0.8;
[0150] In Example 12b, d2 is 30 mm and d2 / d1 is 6.
[0151] Example 13 Group
[0152] This group of embodiments is used to verify the influence of the change of "the vertical distance from the first inorganic particle to the surface of the insulating layer".
[0153] This group of examples is carried out with reference to Example 1, except that different vertical distances from the first inorganic particles to the surface of the insulating layer are obtained by screening, as follows:
[0154] Example 13a, the vertical distance from the boehmite particles to the surface of the insulating layer is 15 μm;
[0155] In Example 13b, the vertical distance from the boehmite particles to the surface of the insulating layer is 2 μm.
[0156] Comparative Example 1
[0157] The process was carried out in accordance with Example 1, except that the median particle sizes of the first inorganic particles and the second inorganic particles were changed, specifically: the first Dv50 was 0.2 μm, the second Dv50 was 5 μm, and the second Dv50 / first Dv50 was 25.
[0158] Comparative Example 2
[0159] The method was carried out in accordance with Example 1, except that the median particle sizes of the first inorganic particles and the second inorganic particles were changed, specifically: the first Dv50 was 5 μm, the second Dv50 was 0.2 μm, and the second Dv50 / first Dv50 was 0.04.
[0160] Comparative Example 3
[0161] The same procedure is carried out as in Example 1, except that the ceramic layer of the separator faces the negative electrode sheet.
[0162] Comparative Example 4
[0163] The same procedure is carried out as in Example 1, except that the first Dv50 = the second Dv50 = 0.5 μm.
[0164] Test Case
[0165] (1) Short circuit rate test
[0166] The batteries prepared in the examples and comparative examples were tested for short circuit rate. The specific test method is as follows: Use a multimeter to adjust to the resistance position, and then connect the positive and negative electrodes of the battery to the test leads respectively. If the test result is 0 ohms, it means that the battery is short-circuited. The short circuit rate is obtained by dividing the number of short circuits tested by the total number of tests (100,000 batteries), and the results are recorded in Table 1.
[0167] (2) Cycle test
[0168] The batteries prepared in the embodiments and comparative examples were subjected to cycle tests, and the specific test method is as follows: the batteries were subjected to charge and discharge cycle tests at a charge rate of 1.5C, a discharge rate of 0.7C, and a voltage window of 3.0V-4.5V (using a blue electric test device) for 800 cycles, and the capacity retention rate was calculated using the first discharge capacity C1 and the 800th cycle discharge capacity C800: C800 / C1×100%; the thickness T1 of the battery charged to 3.9V for the first time (tested using a PPG test device) and the thickness T2 of the battery charged to 4.5V when cycled for 800 cycles were used to calculate the thickness expansion rate (T2 / T1-1)×100%, and the cycle capacity retention rate and thickness expansion rate are recorded in Table 1.
[0169] (3) Lithium deposition test
[0170] The batteries prepared in the examples and comparative examples were subjected to a lithium deposition test. The specific test method is as follows: the batteries were cycled for 800 cycles according to the charge and discharge method in test (2), and then the batteries were disassembled to observe the lithium deposition in the area where the insulating layer on the negative electrode sheet corresponding to the positive electrode sheet covers the positive electrode active layer. The results are recorded in Table 1, where the lithium deposition conditions are ranked from light to heavy: no lithium deposition, slight lithium deposition, lithium deposition, and severe lithium deposition.
[0171] Table 1
[0172]
[0173]
[0174] It can be seen from Table 1 that the lithium ion secondary battery of the present invention has lower short circuit rate and expansion rate and higher cycle capacity retention rate than the comparative example, and improves the lithium plating problem of the battery.
[0175] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A lithium ion secondary battery, characterized in that: It includes a positive electrode sheet, a separator and a negative electrode sheet which are stacked and wound; Along the winding direction of the lithium-ion secondary battery, the current collector of the positive electrode sheet has a positive electrode active layer and an insulating layer; the insulating layer partially covers the positive electrode active layer and partially covers the current collector; the insulating layer includes first inorganic particles, and the median particle size of the first inorganic particles is a first Dv50; The separator includes a substrate layer and a ceramic layer located on at least one side of the substrate layer, the ceramic layer faces the positive electrode sheet; the ceramic layer includes second inorganic particles, and the median particle size of the second inorganic particles is a second Dv50; The second Dv50 / the first Dv50 is 0.25-10, and the second Dv50≠the first Dv50.
2. The lithium ion secondary battery according to claim 1, wherein The second Dv50 / the first Dv50 is 0.25-4; preferably 0.25-3; And / or, the first Dv50 is 0.2 μm-5 μm; preferably 0.5 μm-2 μm; And / or, the second Dv50 is 0.2 μm-5 μm; preferably 0.5 μm-2 μm.
3. The lithium ion secondary battery according to claim 1 or 2, wherein: The insulating layer further includes a first binder, and the ceramic layer further includes a second binder; Preferably, the first binder and the second binder each independently include at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, styrene-butadiene rubber, polymethyl methacrylate, polyacrylic acid, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide and derivatives thereof; Preferably, the first inorganic particles and the second inorganic particles each independently include at least one of magnesium oxide, magnesium hydroxide, aluminum oxide, tungsten oxide, titanium oxide, silicon dioxide and boehmite.
4. The lithium ion secondary battery according to claim 3, wherein: Based on the total mass of the insulating layer, the content of the first binder is 5%-30%; preferably 8%-15%; And / or, based on the total mass of the ceramic layer, the content of the second binder is 1%-20%; preferably 2%-10%; Preferably, the mass content of the first binder in the insulating layer is greater than the mass content of the second binder in the ceramic layer.
5. The lithium ion secondary battery according to claim 3, wherein: The first binder and the second binder both include F element; Preferably, the ratio of the mass content of the F element in the insulating layer to the mass content of the F element in the ceramic layer is 1:(0.2-1.2); more preferably 1:(0.25-0.67).
6. The lithium ion secondary battery according to claim 1 or 2, wherein: The thickness of the positive electrode active layer is 30 μm-75 μm; And / or, the thickness of the insulating layer is 1 μm-15 μm; preferably 3 μm-12 μm.
7. The lithium ion secondary battery according to claim 1 or 2, wherein: In the winding direction of the lithium-ion secondary battery, the size of the insulating layer portion covering the positive electrode active layer is d1, and the size of the insulating layer portion covering the current collector is d2, and d1 and d2 satisfy: d2 / d1 is 0.6-6; preferably 0.85-5; and / or, d1 is 2 mm to 15 mm; And / or, d2 is 4mm-30mm.
8. The lithium ion secondary battery according to claim 1 or 2, wherein: The insulating layer covering the positive electrode active layer is partially embedded in the positive electrode active layer; Preferably, the first inorganic particles are embedded in the positive electrode active layer.
9. The lithium ion secondary battery according to claim 8, wherein: The vertical distance between the first inorganic particles in the insulating layer covering the positive electrode active layer and the surface of the insulating layer is 2 μm-15 μm; Preferably, a vertical distance from the first inorganic particles in the insulating layer covering the positive electrode active layer to the surface of the insulating layer is 3 μm-8 μm.
10. The lithium ion secondary battery according to claim 1 or 2, wherein: The positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a substance with the chemical formula Li a Ni b Co c Mn d M e O2, where 0.8 ≤ a ≤ 1.3, 0.8 ≤ b ≤ 0.98, 0.01 ≤ c ≤ 0.2, 0.005 ≤ d ≤ 0.14, 0 < e ≤ 0.08, and M includes at least one of Al, Zr, B, Y, Sr, W, Ti, Mg, La, Fe, and Nb.
11. The lithium ion secondary battery according to claim 1 or 2, wherein: The insulating layer is located at the winding head end and / or the winding tail end of the positive electrode sheet; And / or, the positive electrode sheet, the separator and the negative electrode sheet are stacked and wound to form a winding core, and the insulating layer is located at the winding head end and / or the winding tail end of the winding core.
Citation Information
Patent Citations
Diaphragm, roll core and battery
CN115275521A
Positive plate and battery
CN118213470A
Positive plate and application thereof
CN118588864A
Separator, electrochemical device, and electronic device
CN119009359A
Lithium secondary battery with improved safety
KR1020150040239A
Cited By
Diaphragm and preparation method thereof, electrode assembly and battery
CN121709865A